Seaweed (Porphyra) cultivation enhances production of autochthonous refractory dissolved organic matter in coastal ecosystems - Wang, Ting; Xu, Jiajun; Dahlgren, Randy A.; Liu, Qiang; Jia, Yang; Chen, Binbin; Xu, Hanqin; Ma, Zengling; Qu, Liyin (Frontiers in Marine Science, 2025)
Seaweed cultivation contributes to coastal carbon sequestration making it a compelling strategy to mitigate global climate change. Porphyra (commonly known as nori) is an economically important seaweed known to have high release rates for biogenic dissolved and particulate organic matter (DOM and POM). However, the impact of Porphyra cultivation on coastal organic matter dynamics remains unclear. To fill this knowledge gap, we conducted investigations examining the quantity and optical properties of DOM and POM, microbial community structures and relevant environmental factors along a continuum from a subtropical river through its adjacent coastal Porphyra cultivation zone during the cultivation and non-cultivation periods. Dissolved organic carbon (DOC) concentration was significantly elevated during the cultivation versus non-cultivation period, while particulate organic carbon (POC) concentration decreased, thereby resulting in a higher DOC/POC ratio in the water column. Endmember mixing analysis further suggested that autochthonous organic matter dominated in the coastal cultivation zone during both periods, with limited inputs of terrestrial organic carbon. Redundancy analysis revealed that more microbial modules mediated organic matter transformations during the cultivation period, leading to a 169% higher estuarine addition of microbially-sourced humic-like C3 compared to the non-cultivation period. Our findings demonstrate that Porphyra cultivation enhanced coastal carbon sequestration by promoting the autochthonous production and transformation of refractory DOM, which has important implications for the sustainable management and development of coastal blue carbon strategies.